2004
DOI: 10.1667/rr3169
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bcl-XSin Radiation Sensitivity

Abstract: Bcl-X(S) is a pro-apoptosis member of the Bcl2 family that has been shown to induce cell death and enhance chemosensitivity. We have investigated the effect of Bcl-X(S) overexpression on radiation sensitivity. Using a tetracycline-repressible system, we found that removal of tetracycline for 16 h induced Bcl-X(S) and reduced the surviving fraction of NIH 3T3 cells to 25%. However, radiation sensitivity was not significantly affected by Bcl-X(S) expression; the mean inactivation doses for Bcl-X(S) repressed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…these results were corroborated by previous findings (Chen et al, 2000;Morgan et al, 2004;Ostruszka and Shewach, 2000;Shewach and Lawrence, 2007). MDA-MB-231 cells showed increased radioresistant to dFdCyd at equimolar concentration and at IC 50 concentration (and more sensitive to radiation only).…”
Section: Discussionsupporting
confidence: 89%
“…these results were corroborated by previous findings (Chen et al, 2000;Morgan et al, 2004;Ostruszka and Shewach, 2000;Shewach and Lawrence, 2007). MDA-MB-231 cells showed increased radioresistant to dFdCyd at equimolar concentration and at IC 50 concentration (and more sensitive to radiation only).…”
Section: Discussionsupporting
confidence: 89%
“…oxygen-dependent radiosensitivity of HeLa cells under our conditions is independent of both Bcl-2 and Bax, consistent with other reports that Bcl-2 proteins [28,29,36,37] and apoptosis [38][39][40] are not important determinants of radiosensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…We found that caspase-9 dominant negative overexpression blocks apoptosis and inhibits gemcitabine-mediated radiosensitization (Figure 2). (However, overexpression of the pro-apoptotic protein bcl-x S in fibroblasts, did not affect gemcitabine radiosensitization (29)). P53 does not seem to have a direct effect on gemcitabine-radiosensitization (30-32).…”
Section: Cellular Effects Of Radiation and Gemcitabinementioning
confidence: 99%